Analisis Perencanaan Pemasaran Menggunakan Metode Least Square di KSU Padurenan Jaya Unit Toko Kain - Ahmad Afendy Susanto; Junirin Junirin; Sudarmin Sudarmin; Kresna Rahma Aji (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
Stock planning and inventory management are crucial to business efficiency, according to this study. Effective inventory management requires accurate sales forecasting. Companies can optimize stock levels, reduce storage costs, and boost efficiency and profitability by forecasting accurately. Previous research has shown that the least squares method can optimize inventory and reduce storage costs. This study forecasts sales using least squares and optimizes stock. Accurate sales forecasts help companies avoid overstocking, boost efficiency, and plan production and distribution. This research is relevant in today's global competition and dynamic business environment. The forecast predicts 1,549 fabric sales in 2025, up from the previous year.